United Kingdom : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in the United Kingdom during 1991-95. Following a brisk expansion in 1994, when the economy achieved a rare combination of above-trend output growth and historically low inflation, the pace of economic activity in the United Kingdom has moderated in the course of 1995. Real GDP growth picked up to an annual rate of 4 percent in the first half of 1994, moderating to 3 1\2 percent in the second half. Real GDP growth slowed further to just more than 2 percent in the first half of 1995.